Conformity of modified O-ring test and maximal pinch strength for cross tape application direction. Issue 22 (June 2018) - Lee, Jung-hoon; Choi, Hyun-su
Abstract: Background: Although cross tape has recently been used by clinicians for various musculoskeletal conditions, scientific studies on the direction of cross tape application are lacking. Methods: The present study aimed to investigate whether the direction of cross tape application affected the outcomes of the modified O-ring test and maximal pinch strength using a pinch gauge and the conformity between these 2 tests when cross tape was applied to the forearm muscles of individuals with no upper extremity pain and no restriction of joint range of motion. This study used a single-blinding crossover design. The subjects comprised 39 adults (16 men and 23 women). Cross tape was applied to the dominant hand so that the 4 rows were at an angle of 45° to the right or left of the direction of the flexor digitorum superficialis muscle fibers, and then the subjects underwent a modified O-ring test and a test of maximal pinch strength using a pinch gauge. Both tests were performed in both directions, and the order of the directions and tests was randomized. SPSS 18.0 was used for statistical analysis. Cohen's kappa coefficient was used to analyze the conformity of the results from the 2 tests. The statistical significance level was P < .05. Results: A positive response in the modified O-ring test and maximal pinch strength were both affected by cross tape direction. The modified O-ring test and maximal pinch strength using pinch gauge results were in agreement ( P < .00), and the kappa coefficient was significant at 1.00. Conclusion: The direction of cross tape application that produced a positive response in the modified O-ring test also produced greater maximal pinch strength. Thus, we propose that when applying cross tape to muscles, the direction of the 4 lines of the cross tape should be 45° relative to the direction of the muscle fibers, toward the side that produces a positive response in the modified O-ring test or produces the greatest maximal pinch strength using a pinch gauge.